The nature of jets: evidence from circular polarization observations - Wardle, J; Homan, D (2002)
We review recent observations of circularly polarized radiation from AGN made with the VLBA and with the ATCA. We also discuss briefly the detections of the Galactic sources Sgr A* and SS 433. The origin of the circular polarization is still an open question in most cases, and we discuss four possible mechanisms. Detectable circular polarization is a common property of quasars, but not of radio galaxies, and is always associated with the compact core. There is growing evidence that the sign of the circular polarization stays the same over at least 20 - 30 years, suggesting that it is a fundamental property of the jet.